Safety and efficacy of pitolisant on cataplexy in patients with narcolepsy: a randomised, double-blind, placebo-controlled trial. Issue 3 (March 2017) - Szakacs, Zoltan; Dauvilliers, Yves; Mikhaylov, Vladimir; Poverennova, Irina; Krylov, Sergei; Jankovic, Slavko; Sonka, Karel; Lehert, Philippe; Lecomte, Isabelle; Lecomte, Jeanne-Marie; Schwartz, Jean-Charles; ,
Summary: Background: Histaminergic neurons are crucial to maintain wakefulness, but their role in cataplexy is unknown. We assessed the safety and efficacy of pitolisant, a histamine H3 receptor inverse agonist, for treatment of cataplexy in patients with narcolepsy. Methods: For this randomised, double-blind, placebo-controlled trial we recruited patients with narcolepsy from 16 sleep centres in nine countries (Bulgaria, Czech Republic, Hungary, Macedonia, Poland, Russia, Serbia, Turkey, and Ukraine). Patients were eligible if they were aged 18 years or older, diagnosed with narcolepsy with cataplexy according to version two of the International Classification of Sleep Disorders criteria, experienced at least three cataplexies per week, and had excessive daytime sleepiness (defined as an Epworth Sleepiness Scale score ≥12). We used a computer-generated sequence via an interactive web response system to randomly assign patients to receive either pitolisant or placebo once per day (1:1 ratio). Randomisation was done in blocks of four. Participants and investigators were masked to treatment allocation. Treatment lasted for 7 weeks: 3 weeks of flexible dosing decided by investigators according to efficacy and tolerance (5 mg, 10 mg, or 20 mg oral pitolisant), followed by 4 weeks of stable dosing (5 mg, 10 mg, 20 mg, or 40 mg). The primary endpoint was the change in the average number of cataplexy attacks per week as recorded in patient diaries (weekly cataplexy rate [WCR]) between the 2 weeks of baseline and the 4 weeks of stable dosing period. Analysis was by intention to treat. This trial is registered withClinicalTrials.gov, numberNCT01800045 . Findings: The trial was done between April 19, 2013, and Jan 28, 2015. We screened 117 patients, 106 of whom were randomly assigned to treatment (54 to pitolisant and 52 to placebo) and, after dropout, 54 patients from the pitolisant group and 51 from the placebo group were included in the intention-to-treat analysis. The WCR during the stable dosing period compared with baseline was decreased by 75% (WCRfinal =2·27; WCRbaseline =9·15; WCRfinal/baseline =0·25) in patients who received pitolisant and 38% (WCRfinal =4·52; WCRbaseline =7·31; WCRfinal/baseline =0·62) in patients who received placebo (rate ratio 0·512; 95% CI 0·43–0·60, p<0·0001). Treatment-related adverse events were significantly more common in the pitolisant group than in the placebo group (15 [28%] of 54 vs 6 [12%] of 51; p=0·048). There were no serious adverse events, but one case of severe nausea in the pitolisant group. The most frequent adverse events in the pitolisant group (headache, irritability, anxiety, and nausea) were mild or moderate except one case of severe nausea. No withdrawal syndrome was detected following pitolisant treatment; one case was detected in the placebo group. Interpretation: Pitolisant was well tolerated and efficacious in reducing cataplexy. If confirmed in long-term studies, pitolisant might constitute a useful first-line therapy for cataplexy in patients with narcolepsy, for whom there are currently few therapeutic options. Funding: Bioprojet, France.